Clinicopathological features affecting the efficacy in 131I ablation therapy of papillary thyroid carcinoma with lymph node metastasis - Xu, Xiang; Li, Chengqian; Yu, Xiaolong; Wang, Guoqiang; Guo, Yanjun; Ni, Huaiwen; Zhao, Wenjuan; Wang, Yangang; Dong, Bingzi (Frontiers in Endocrinology, 2024)
Background Lymph node metastasis is the major cause of increased recurrence and death in patients with papillary thyroid carcinoma (PTC). We evaluate the clinicopathologic factors affecting excellent response (ER) in patients with PTC with lymph node metastasis following operation and 131I ablation therapy. Methods A total of 423 patients with PTC with lymph node metastasis who underwent thyroidectomy and postoperative 131I ablation therapy were enrolled. The relationship between clinicopathological factors affecting ER achievement was analyzed. Results Multivariate analysis showed that the foci diameter (≤1 cm), unifocal, combination with Hashimoto’s thyroiditis (HT), lymph node metastases rate (LR) (≤40%), no postoperative lymph node metastasis, low preablative stimulated thyroglobulin (ps-Tg) level (≤3.87 ng/mL), and the time of 131I ablation therapy (one time) were positively correlated with the ER achievement [odds ratio (OR): 1.744, 3.114, 3.920, 4.018, 2.074, 9.767, and 49.491, respectively; all p < 0.05]. The receiver operating characteristic (ROC) curves showed that the cutoff values of ps-Tg and LR were 4.625 ng/mL and 50.50%, respectively. The AUC of ROC of ps-Tg and LR for predicting ER achievement was 0.821 and 0.746, respectively. The Tg and the cumulative risk of non-ER elevated with the increase of LR, especially for the high-level ps-Tg (>4.625 ng/mL) group. Conclusion The foci diameter and number, combination with HT, LR, and ps-Tg level are independent factors for ER. Ps-Tg level and LR are valid predictive factors for the efficacy of 131I therapy in patients with PTC. The predictive value of the cumulative risk of non-ER can be improved by the combination of ps-Tg and LR.